Olfactory learning and memory in the bumblebee Bombus occidentalis (2009)
In many respects, the behavior of bumblebees is similar to that of the closely related honeybees, a long-standing model system for learning and memory research. Living in smaller and less regulated colonies, bumblebees are physiologically more robust and thus have advantages in particular for indoor experiments. Here, we report results on Pavlovian odor conditioning of bumblebees using the proboscis extension reflex (PER) that has been successfully used in honeybee learning research. We examine the effect of age, body size, and experience on learning and memory performance. We find that age does not affect learning and memory ability, while body size positively correlates with memory performance. Foraging experience seems not to be necessary for learning to occur, but it may contribute to learning performance as bumblebees with more foraging experience on average were better learners. The PER represents a reliable tool for learning and memory research in bumblebees and allows examining interspecific similarities and differences of honeybee and bumblebee behavior, which we discuss in the context of social organization